Digital platforms as a tool for the development of social entrepreneurship in the Republic of Kazakhstan - Gelashvili, N.N.; Temirbayeva, D.M. (KSU Publ., 2020)
In the modern economy, information technologies are becoming important. They penetrate all sectors of the economy of Kazakhstan. Currently, one of the important directions of increasing the social orientation of the state to solve the problems of society is social entrepreneurship. This trend is observed not only in Kazakhstan, but also in other countries of the world. Social entrepreneurship is based on business platforms. Business processes in social entrepreneurship are based on them. Therefore, it is important to find modern methods for optimizing business models. One of the tools is crowdfunding.
Keywords: social entrepreneurship; non-profit organizations; monetization of social projects; socially responsible business; crowdfunding